An Ethno-phenomenological Study of Pregnant Women's Experiences regarding Household Roles - Fatemeh Erfanian Arghavanian; Abbas Heydari; Mohsen Noghani Dokht Bahmani; Robab Latifnejad Roudsari (Shiraz University of Medical Sciences, 2020)
Background: Household labor has been indicated as a feminine role even in the present millennium, in which gender role orientations have been changed. As pregnancy is an important time for studying the division of household labor, this study aimed to discover the meaning of the pregnant women's experiences of household roles. Methods: An ethno-phenomenological study, in which van Manen approach to phenomenology was its core and focused ethnographic approach was its supplementary component, was used to conduct this study. 25 pregnant women with maximum variation were recruited via the purposeful sampling during 2016-2017 in Mashhad, Iran. In-depth semi-structured interviews, vignette interviews as well as observations were used for data collection. Six-step van Manen's descriptive-interpretive phenomenological approach was used for concurrent data collection and analysis. MAXQDA, version 10, was used for data organization. Results: Data analysis led to the emergence of an overarching theme entitled: "couples' preservation, keeping up and protection of the household roles". This was derived from two subthemes including the mother's efforts to play the household roles and spouse confrontation with the household chores. Conclusion: The consequence of all endeavors of pregnant women along with their husbands develops the experience of preserving and maintaining the importance of household roles. As pregnancy is an important period for considering division of household responsibilities, it is necessary to design and implement gender sensitive programs to empower pregnant women and their families as well.